Effectiveness of Localized English Reading Materials in Enhancing the Reading Skills of the Grade two Pupils - Shermaine D. Rafael; Victoria E. Tamban (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
Students today are 21st-century learners who prefer digitization and reading is not their top priority, teachers at the same time should meet the needs of these students. English teachers, specifically in reading skills, should have the capability and knowledge to craft methods to use in dealing with students who have difficulty with reading. This study aimed to determine the effectiveness of localized english reading materials in enhancing the reading skills of grade two pupils. The reading skills of the pupils in this research were determined through match pairing. The participants came from the total population of 32 pupils from section orange in grade two, who were grouped into two through match pairing based on their pretest results. There was 16 match paired pupil-participants included in this study. These pupil-participants were the advisees of the researcher for the school year 2021-2022 in modular distance learning. Another group of respondents were the 20 teacher-validators who assessed the crafted localized reading materials using the survey questionnaire. The pretest showed that both groups are at the beginning level in terms of their reading skills. The findings of this study indicated that the experimental group got much higher mean scores than the comparison group on their formative and post-test. The computed t-values for lesson 1 gained a t-value of 2.368, lesson 2 with a t-value of 2.885; lesson 3 with a t value of 5.085; and lesson 4 having a t-value of 8.259 showed extremely significant differences between the formative means scores of the participants. A similar result found a highly significant difference between the post-test mean scores performance of the experimental group and the comparison group with a t-value of 3.966 and a p-value less than 0.01 level of significance. All results indicated the rejection of null hypotheses and acceptance of alternative ones. These findings implied that teachers must use tactics and practices such as learning by doing, manipulative, and practical learning to integrate localization and contextualization into the teaching-learning process. Keywords: localized English reading materials, reading skills, teaching-learning process